2016
DOI: 10.3201/eid2209.151164
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Convalescent Plasma Immunotherapy for MERS-CoV Infection, Saudi Arabia

Abstract: Efficacy testing will be challenging because of the small pool of donors with sufficiently high antibody titers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
230
1
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(243 citation statements)
references
References 25 publications
2
230
1
10
Order By: Relevance
“…However, in a longitudinal study of MERS survivors in Jeddah, Saudi Arabia, only two out of nine survivors remained positive for MERSspecific antibodies when tested 18 months after illness onset (Alshukairi et al, 2016). Furthermore, Arabi and colleagues (Arabi et al, 2016) reported that only 4 (36.7%) of 11 healthcare workers who had a history of laboratory-confirmed MERS-CoV infection had detectable MERS-CoV-antibody levels by ELISA a median of 381 days after infection. These data indicate that MERS-CoV-antibody levels decline more rapidly, compared to SARS-CoV survivors.…”
Section: Current Knowledge Of Adaptive Immune Responses To Mers-covmentioning
confidence: 99%
“…However, in a longitudinal study of MERS survivors in Jeddah, Saudi Arabia, only two out of nine survivors remained positive for MERSspecific antibodies when tested 18 months after illness onset (Alshukairi et al, 2016). Furthermore, Arabi and colleagues (Arabi et al, 2016) reported that only 4 (36.7%) of 11 healthcare workers who had a history of laboratory-confirmed MERS-CoV infection had detectable MERS-CoV-antibody levels by ELISA a median of 381 days after infection. These data indicate that MERS-CoV-antibody levels decline more rapidly, compared to SARS-CoV survivors.…”
Section: Current Knowledge Of Adaptive Immune Responses To Mers-covmentioning
confidence: 99%
“…Thus, the pool of healthy subjects with sufficient neutralizing antibody titer in convalescent plasma might be very limited. Finally, the hyperimmune plasma used in this study had a high neutralizing antibody titer of 3840, whereas at best human convalescent plasma has neutralizing antibody titers of 320e800 (Park et al, 2015;Arabi et al, 2016) (these studies use different methods to measure neutralizing antibodies). It is unclear whether convalescent plasma with lower neutralizing titers would have a similar effect on disease progression, as lower neutralizing antibody titers in the circulation will likely be reached.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study suggests that the availability of donors with sufficiently high MERS-CoV antibody titers might be limited; only 12 out of 443 tested sera obtained from patients, healthcare workers and household contacts were positive on ELISA (Arabi et al, 2016). Furthermore, it has been suggested that severity of disease is linked to serological response; in patients who developed severe disease upon infection with MERS-CoV higher neutralizing antibody levels were detected, whereas in patients with mild or subclinical disease lower and potentially short-lived neutralizing antibody levels were detected (Drosten et al, 2014;Park et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The three most frequent symptoms are: fever (77% [IQR: 59-82]), cough (90% [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]), and dyspnea (68% ).…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…The efficacy and safety of plasma from convalescent patients have not been assessed. Three separate reports concluded that such therapeutic approaches were inappropriate [63]. One trial is listed on www.clinicaltrials.gov.…”
Section: Convalescent Plasmamentioning
confidence: 99%